Mapping (for) resilience across city scales: An opportunity to open-up conversations for more inclusive resilience policy?. Issue 99 (September 2019) - Borie, Maud; Ziervogel, Gina; Taylor, Faith E.; Millington, James D.A.; Sitas, Rike; Pelling, Mark
Highlights: Interrogation of the use of spatial knowledge for resilience building in Cape Town and Nairobi. Mapping practices are heterogeneous, producing diverse understandings of resilience. Through maps diverse actors, scales and forms of knowledge can be connected. Knowledge systems can both open-up and close down governance options. There is value in using diverse methods to open up conversations on resilience to bring in more actors and perspectives. Abstract: There are growing calls, across a continuum from international agreements to social movements, for strengthening urban resilience alongside reductions in inequality and poverty. Although there is broad agreement on what the term resilience means in general, different perspectives exist on how the concept should be implemented locally and controversies around its transformative potential continue. While differing social and institutional factors are important, the ways in which knowledge practices produce these diverse perspectives have been overlooked. To address this gap, this paper focuses on the role of spatial knowledge and mapping practices for resilience and disaster risk reduction. Traditionally, much of the spatial data used for planning has been quantitative and at broad, city-level scales. However, although experiential understandings of resilience have been widely identified, there have been few attempts to integrate these perspectives, often relying on qualitative andexperiential knowledge, into city-level resilience planning. Bringing together insights from Science and Technology Studies and Human Geography, this paper explores the opportunities that different mapping techniques provide for resilience thinking and planning. Our starting point is that science and technology are not neutral for governance and can both open up or close down governance options. Using case studies from Nairobi and Cape Town, our findings show that mapping practices are heterogeneous and produce diverse understandings of resilience. Although traditional methods dominate city mapping in these case studies, we find innovation at both the city and finer spatial scales. Maps and mapping offer opportunities for resilience via connecting diverse actors, scales and forms of knowledge. We suggest that more work is needed on how to include non-traditional methods, from those that value local experience and the voice of the marginalized to more quantitative mapping methods. While fully integrating diverse approaches may not be possible, nor desirable, bringing them into conversation helps open-up deliberative spaces for resilience.